Mitigation of am interference in digital transmission - Sulaiman, Erwan (2004)
The plain-old-telephone-system (POTS) is now increasingly used to carry high-speed data such as for Internet purpose. However, problem can occur if the telephone network is in close proximity to an AM radio transmitter, transmitting high power signal at a frequency which overlaps the bandwidth of the Internet transmission. The interfering electromagnetic field can induced enough current and voltage in the telephone network and causing significant data errors. This report presents a study on the effects of high-powered AM transmission at 576 kHz on a digital transmission system. A GTEM Cell was used to generate the 576kHz clectric field intensity varying from lV/m to 15 V/m with 80% amplitude modulation. The electric field is imposed on a section of the cable and the Bit Error Rate (BER) is noted using Data Tools 5000. Shielding technique was employed using four conducted materials (soft steel, hard steel, aluminum and copper) in order to test the attenuation of the electric field reaching the cable. Measured results showed that copper (a= 5.87 x 107 S/m, fr =1) can reduce up to 70% of the BER. The relationship between electric field E and BER for copper is expressed as BER = 2 x 10~5 e0-3"^' +2.48x10"^ indicating that the BER increases exponentially with the magnitude of the applied electric field. It is obvious from the work done in this project that any network situated near a high-powered electromagnetic field transmitter should employ a good shielded cabling system. It is recommended that further study need to be carried out to find ways of mitigating the effects of the interfering field such filtering and grounding.